Exploring Audit Delay In Indonesian Energy Sector Companies: Assessing The Relevance Of Public Accounting Firm Size - Jannah D , Khairunnisa Al-qur'aini Nur; Kholid, Muamar Nur (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2025)
This study aims to determine the effect of Operational Complexity, Company Size, Audit Tenure, Cap Size, Company Age, Profitability, and Leverage on Audit Delay. This quantitative study uses a population of energy sector companies listed on the IDX in 2019-2022. The data collected is secondary data. The samples in this study used a purposive sampling method, and 52 companies that met the criteria were obtained. This research uses a multiple linear regression method using SPSS software. This research indicates that Public Accounting Firm Size has a significant negative effect on Audit Delay. In contrast, Operational Complexity, Audit Tenure, and Company Size do not affect Audit Delay